THE DYNAMICS OF THE PEOPLE'S ECONOMY: A SYNTHESIS OF LITERATURE REVIEW ON GRASSROOTS ECONOMIC DEVELOPMENTMODELS - Kholid Ansori; Sri Mulyono; Iwan Kusnadi (Adiba Aisha Amira, 2023)
The community-based economic development model is an approach that emphasises the active participation of local communities in planning, implementing and managing economic projects in their neighbourhoods. The study conducted in this research used the literature research method. The findings indicate that access to technology and information, education and training, and government policy support are the main factors that drive community economic growth. Digital technology provides opportunities for micro, small and medium enterprises to improve marketing and operational efficiency, while education improves vital managerial skills. Government policies that support micro, small, and medium enterprises, including licensing simplification, tax incentives, and training programmes, play a significant role in the development of small businesses. Adequate infrastructure and access to finance from microfinance institutions have also been shown to support the economic dynamism of communities. However, the study also identified various constraints that slow down the economic growth of communities, such as limited access to capital, complex regulations, and inadequate infrastructure. Low financial literacy hampers good financial management among small business owners. In addition, tough challenges come from fierce competition with large companies and negative perceptions of local products. These constraints necessitate effective collaboration between the government, the private sector and the community to create a more conducive business environment for micro, small and medium enterprises. With an integrated and sustainable approach, the economic potential of the community can be optimised for mutual prosperity.